2004
DOI: 10.1103/physrevlett.93.196102
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evidence for a Partially Dissociated Water Bilayer on Ru{0001}

Abstract: Core-level photoelectron spectra, in excellent agreement with ab initio calculations, confirm that the stable wetting layer of water on Ru[0001] contains O-H and H2O in roughly 3:5 proportion, for OHx coverages between 0.25 and 0.7 ML, and T<170 K. Proton disorder explains why the wetting structure looks to low energy electron diffraction (LEED) to be an ordered p(square root of 3 x square root of 3)R30 degrees adlayer, even though approximately 3/8 of its molecules are dissociated. Complete dissociation to at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
106
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(114 citation statements)
references
References 26 publications
7
106
1
Order By: Relevance
“…These results are consistent with other work that found that OH constitutes only 30% Ϯ 10% of the coverage of the mixed H 2 O -OH structure on Ru͑0001͒ formed either thermally or by electron bombardment, and also by coadsorption of H 2 O ͑D 2 O͒ with small amounts of atomic O. [13][14][15]35 The XAS at the O 1s edge gives information on the O 2p unoccupied electronic states. Using the polarization dependence of the absorption process, we obtain information on bond orientation.…”
Section: Theoretical Methodssupporting
confidence: 80%
See 1 more Smart Citation
“…These results are consistent with other work that found that OH constitutes only 30% Ϯ 10% of the coverage of the mixed H 2 O -OH structure on Ru͑0001͒ formed either thermally or by electron bombardment, and also by coadsorption of H 2 O ͑D 2 O͒ with small amounts of atomic O. [13][14][15]35 The XAS at the O 1s edge gives information on the O 2p unoccupied electronic states. Using the polarization dependence of the absorption process, we obtain information on bond orientation.…”
Section: Theoretical Methodssupporting
confidence: 80%
“…All electronic interactions are approximated with the extended Hückel theory ͑EHT͒, with the associated parameters ͑on-site energies and Slater orbitals͒ obtained after fitting the EHT electronic structure to that derived from the ab initio DFT calculations. 34 Figure 1͑a͒ shows the O 1s XPS region of a surface prepared by dosing ϳ2 L H 2 O at 180 K. We observe an O 1s peak at 530.8 eV due to OH and a 532.3 eV peak due to molecular H 2 O, 13,15,35 which provides evidence that the phase formed by annealing H 2 O at 180 K contains both H 2 O and OH. Calibrating against the ϳ0.67 ML saturation coverage of the metastable intact water monolayer obtained by desorbing water multilayers from a sample at 150 K, 13,15 the total O coverage in the mixed phase deduced from the O 1s peak area is 0.22Ϯ 0.02 ML, of which OH constitutes 23Ϯ 3%.…”
Section: Theoretical Methodsmentioning
confidence: 85%
“…Two of them, both utilizing XPS with synchrotron radiation, came to fully opposite results [25,26]. Reference 25 reported XPS data indicating partial dissociation of H 2 O and D 2 O at 145 K from the beginning, whereas Ref.…”
Section: O + Oh + H (D 2 O + Od + D)mentioning
confidence: 99%
“…In a later publication this ratio had been changed to 5:3 in order to fit XPS results [25]. The low chemisorption energy of the molecular layer and the resulting «nonwetting» argument of [24,25] have been questioned on the basis of more refined DFT calculations and experiments (see, e.g., [22] and references therein). There is agreement now that for both H 2 O and D 2 O the pure layers before the start of desorption are molecular, i.e., water does wet the Ru surface.…”
Section: O + Oh + H (D 2 O + Od + D)mentioning
confidence: 99%
“…[4][5][6][7][8] In this system dissociation is an activated process as water adsorbs molecularly at temperatures below ~140 K. At low temperature dissociation can be activated by energetic electrons, as found in low energy electron diffraction (LEED) or in x-ray photoemission spectroscopy (XPS). 6,7,9 It can also be promoted by interaction with other adsorbates. 8,10,11 On Cu(111) and Cu(100), dissociation of water has been observed by using tunneling electrons at energies above ∼1.5 eV.…”
Section: Introductionmentioning
confidence: 99%